Detecting and managing drug-related problems in the neurology ward of a tertiary care teaching hospital in Iran: A clinical pharmacist's intervention - Farzaneh Foroughinia; Seyyed Ramtin Tazarehie; Peyman Petramfar (Wolters Kluwer Medknow Publications, 2016)
Objective: Nowadays, the role of clinical pharmacists has become more prominent by more clinical pharmacists joining the health-care teams. This study was aimed to assess the role of a clinical pharmacist specialist in detecting and managing drug-related problems (DRPs) in the neurology ward of a tertiary care teaching hospital in Iran. Methods: This is a prospective cross-sectional study conducted on 123 hospitalized patients admitted to the neurology ward of a teaching hospital. The clinical pharmacist visited the patients and filled out the designed pharmacotherapy sheet for each patient. Then, the general pharmacist checked the patients' files and pharmacotherapy sheets and categorized DRPs using modified method of "The Pharmaceutical Care Network Europe classification, Version 5.01." Findings: A total of 168 errors were found and 346 interventions were done by the clinical pharmacist during the study period. The most common form of errors in our study was "drug choice problems" (57.76%). The acceptance rate of interventions was 41.91% among physicians. Conclusion: The large number of interventions reported in several studies, as well as this study, revealed that clinical pharmacy services could contribute to a rationalization of drug therapy and may eventually lead to more medication safety.